Morality and mortality why the Church of England would have rejected Walzer's supreme emergency argument - Schawarz, Michael; Comer, Debra R. 1960- (2018)
Walzer insists that his supreme emergency argument morally legitimises Churchill's 1940 decision to bomb German civilians. We contend, however, that it is morally deficient. We contend, further, that if Walzer's argument had been presented to the leaders of the Church of England in 1940 as justification for the bombing of German civilians, the Church leadership would have rejected it. According to Walzer, a supreme emergency forces us to waive rights we would honour under ordinary circumstances. But the Church has a different conception of rights. Because the Church is committed to universal rights - which are inviolable and cannot be overridden - it would never have agreed with Walzer. Our discussion as to those conflicting conceptions of rights illustrates what differentiates biblical ethics from secular ethics.
Keywords: Church of England; Walzer; Ethics; Rights; supreme emergency